Chemical synthesis of a two‐domain scorpion toxin LaIT2 and its single‐domain analogs to elucidate structural factors important for insecticidal and antimicrobial activities. (4th November 2018) - Juichi, Hironori; Ando, Ryo; Ishido, Takafumi; Miyashita, Masahiro; Nakagawa, Yoshiaki; Miyagawa, Hisashi
Abstract : Scorpion venom contains various bioactive peptides. Among them, peptides having two different structural domains constitute a toxin family known as β‐KTx or scorpine‐like peptides. These peptides consist of an α‐helical structure in the N‐terminal region and a cysteine‐stabilized structure in the C‐terminal region. This unique structure of β‐KTx peptides contributes to their diverse biological functions, but the importance of each domain for their activities is not fully understood. LaIT2 is a β‐KTx peptide isolated from the venom of the scorpion Liocheles australasiae, which shows both insecticidal and antimicrobial activities. In this study, we chemically synthesized full‐length LaIT2 using a native chemical ligation technique as well as its N‐terminally or C‐terminally truncated single‐domain analogs to evaluate structural factors important for the activities. Biological evaluation of these peptides revealed that the N‐terminal α‐helical domain of LaIT2 is essential for the expression of both insecticidal and antibacterial activities. This suggests that the disruption of membrane structures largely accounts for the biological activities of LaIT2. Abstract : In this study, we synthesized a two‐domain scorpion toxin LaIT2 using a native chemical ligation method. We also synthesized single‐domain peptides and evaluated their insecticidal and antibacterial activities. The result showed that the N‐terminal domain of LaIT2 is essential for the expression of both activities. Since the N‐terminal domain adopts an amphipathic alpha‐helical structure, these activities are likely to be caused by disruption of the cellular membrane structure.